Positive behavioural support at schools via designing supportive learning environments - Skura, Monika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The following paper examines assumptions, application and efficacy of positive behavioural interventions and supports (PBIS) which have been widely used in the United States over the past two-decades. The author addresses a significant area of activities carried out within the framework of PBIS, which concerns engineering supportive learning environments. The author also aims to indicate the most important elements of the model that could be applied in the educational activities of the Polish school.